By faith alone answering the challenges to the doctrine of justification - Johnson, Gary L.W. 1950-; Waters, Guy Prentiss, 1975- (Wheaton, IL Crossway, 2006)
Includes bibliographical references and indexes.
Keywords: Justification (Christian theology).